(untitled) (Research, Society and Development, 2021)
Objective: To analyze the use of physical therapy resources, such as Vacuum Therapy and Microgalvanopuncture in the direct treatment of atrophic streaks. Methods: This is a descriptive, cross-sectional systematic review. Based on a survey carried out on the digital platforms Scielo, Academic Google and periodic Capes. The articles found were in the Portuguese language. The inclusion criteria used were articles that presented case studies with the theme of the application of therapeutic resources in the treatment of atrophic streaks. Results: In general, the studies showed promising results regarding the use of therapeutic resources in individuals who reported having atrophic streaks in some body area.